Ammonia volatization from conventional and stabilized fertilizers, agronomic aspects and microbiological attributes in a Brazilian coffee crop system - Sarkis, Leonardo Fernandes; Dutra, Mateus Portes; Oliveira, Damiany Pádua; Fernandes, Tales Jesus; de Souza, Thaís Regina; Builes, Victor Ramirez; Guelfi, Douglas (Frontiers in Plant Science, 2023)
We aimed to quantify the N losses through volatilization of the main conventional and stabilized N fertilizers applied in coffee plantations. Additionally, we also assessed microbiological attributes of the soil (microbial biomass carbon (MBC); microbial biomass nitrogen (MBN); microbial basal respiration (MBR); metabolic quotient (qCO2); urease, β-glucosidase, acid phosphatase, and arylsulfatase activities) and agronomic aspects of the crop (N content in the leaves and beans, yield, and N exportation by the beans). Treatments consisted of the combination of three fertilizers (ammonium nitrate - AN, conventional urea - U, and urea with N- (n-butyl) thiophosphoric triamide (NBPT) - UNBPT, and five doses of N (0, 150, 275, 400, and 525 kg ha-1 year-1 of N), with four replicates, totalling 60 experimental plots. In the two crop seasons evaluated, daily and cumulative losses of N-NH3 from the split fertilizer applications were influenced by the N fertilizer technologies. The application of U resulted in losses of 22.0% and 22.8% for the doses of 150 and 400 kg ha-1 year-1 of N. This means that 66 and 182 kg ha-1 of N-NH3 were lost, respectively, at the end of six fertilizations with U. UNBPT reduced urease activity and N-NH3 losses compared to conventional urea, avoiding the volatilization of 15.9 and 24.3 kg ha-1 of N. As for AN, N-NH3 losses did not exceed 1% of the applied dose, regardless of the weather conditions during the fertilization. Urease activity was higher on days of maximum NH3 volatilization. There was an effect of the N sources (NS), soil sampling time (ST), and their interaction (NS × ST) on the MBN and arylsulfatase activity. The N sources also influenced the MBC and the qCO2. A substantial amount of N was removed from the system by the beans and husks of the harvested fruits. Our study showed that N fertilizer technologies are interesting options to reduce N-NH3 losses by volatilization, increase N retention in the soil, and improve microbiological attributes and the sustainability of coffee production systems.